Design and performance analysis of a long-stroke electromagnetic double-reel hammer - Alkasassbeh, Jawdat S.; Pavlov, Vlademer Е.; Al-Zyoud, Khalaf Y.; Al-Awneh, Tareq A.; Alkasassbeh, Osamah; Al-Rawashdeh, Ayman Y. (Institute of Advanced Engineering and Science, 2024)
This paper comprehensively investigates the performance characteristics of a long-stroke electromagnetic double-reel hammer compared to a conventional hammer. Quantitative analysis indicates that the long-stroke hammer shows a significant increase in striker speed and impact energy. The impact energy has increased by 255%, and energy losses in copper windings have decreased by 124% per operating cycle. Additionally, the long-stroke hammer demonstrates a 105% reduction in energy consumption and a 52% improvement in overall efficiency per cycle compared to the conventional hammer. This study examines the operational characteristics of the long-stroke hammer throughout its cycle using field theory methods, MATLAB simulations, and experimental tests. Results indicate higher impact energy and speed, lower energy losses in copper windings, and higher efficiency per cycle for the long-stroke hammer. Furthermore, a mathematical model of the long-stroke hammer is developed, incorporating static parameters and oscillograms of striker movement and current flow. A comprehensive comparison of the performance indicators of both hammers reveals significant improvements in lifting height, cycle duration, impact frequency, and striker speed for the long-stroke hammer. Overall, these findings suggest that the long-stroke operating mode can significantly enhance the efficiency and performance of conventional hammers while simultaneously reducing impact frequency and machine heating.